2022
DOI: 10.3390/cryst12030409
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Spectral Properties of DBR-Based Photonic Crystal Structure for Optical Filter Application

Abstract: In this work, the spectral properties of distributed Bragg reflector-based photonic crystal (DBR-PhC) structures were studied for the near-infrared (NIR) range. Different structural properties were varied to study their effect on the quality of the stopband and the appearance of the resonant dips in the reflection spectra of the DBR-PhC structure. The investigated structural features included the depth of PhC holes, hole radius, and number of PhC elements in the DBR structure. The 11-layered DBR structure was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The authors reported a 40 nm tuning (625-665 nm) for an applied maximum voltage of 50 V [26]. A distributed Bragg reflector-based (DBR) optical filter working as an alternative to the well-known Fabry-Pérot filters for a NIR region is proposed by Ahmed et al [27] and the authors reported a FWHM of around 0.016 of filtered wavelength. A similar structure working on a guided-mode resonance principal is also explored to work as a Fano filter device [28].…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported a 40 nm tuning (625-665 nm) for an applied maximum voltage of 50 V [26]. A distributed Bragg reflector-based (DBR) optical filter working as an alternative to the well-known Fabry-Pérot filters for a NIR region is proposed by Ahmed et al [27] and the authors reported a FWHM of around 0.016 of filtered wavelength. A similar structure working on a guided-mode resonance principal is also explored to work as a Fano filter device [28].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, photonic crystals (PhCs) are also one of the most significant contenders serving as nanostructures that are capable of controlling light at wavelength scales [ 14 ]. PhCs are found in nature [ 15 ] and can be designed and fabricated artificially as per the specification of the device, i.e., optical sensors [ 16 ], nanowires [ 17 ], DBRs [ 18 ], waveguides [ 19 ], and optical filters [ 20 ]. However, recently, the localized surface plasmon polariton (LSPP) has gained the attention of researchers both in the field of academia and industry due to their nature of high sensitivity [ 21 ] and simplified materials usage [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…They exhibit different phenomena of light in terms of reflection, refraction, diffraction, and total internal reflection [14]. PhCs can be created artificially to design, produce and achieve what is required of a certain component or a device in the existing world [15].…”
Section: Introductionmentioning
confidence: 99%